Sustentabilidade municipal no contexto de uma política pública de controle do desmatamento no Pará - Francisco do Vale, Francinelli Angeli; Toledo, Peter Mann de; Vieira, Ima Célia Guimarães; Santos Junior, Roberto Araújo Oliveira (Economía Sociedad y Territorio, 2019)
This work analyzed sustainability performance of 26 municipalities in the so-called amazon arch of deforestation in the state of Pará, Brazil in the years 2000 and 2010, using the Sustainability Barometer with 31 indicators in social, economic and environmental dimensions. The results show that Altamira and Novo Progresso have intermediate performance in two years and five municipalities progressed to the intermediate level in 2010 while the other remained in a critical situation. There was a slowdown in deforestation in municipalities, but despite the positive results achieved, they were unsatisfactory to change the sustainability status of municipalities